The Factors Influencing Sustainable Investment in Digital Investment Applications in Indonesia - Hati, Elyana; Sihombing, Pardomuan (International Journal of Social and Management Studies, 2025)
This study investigates the determinants of sustainable investment behavior among Indonesian investors who use digital investment applications. Specifically, the research examines the effects of risk preference and investment horizon on sustainable investment, with income, gender, and age as moderating variables. The study employed a quantitative research method with 85 respondents from the Master of Management program at Universitas Mercu Buana, Jakarta. Partial Least Squares Structural Equation Modeling (PLS-SEM) was utilized for data analysis. The findings reveal that both risk preference and investment horizon have a significant positive effect on sustainable investment decisions. However, income, gender, and age do not moderate these relationships. This research contributes to the literature by emphasizing the stronger role of behavioral factors compared to sociodemographic characteristics in shaping sustainable investment behavior in the Indonesian digital financial market.